MUHASSINĀT AL-MA‛NAWIYYAH FĪ SŪRATI AL-WĀQI‛AH - Syahbani, Riyanto (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
BadÄ« â€™as the study of the beauty of a sentence, in which it is related to the beauty of language style and is called muhassinat. This study aims to analyze muhassinÄt al-maâ€™nawiyah on surah Al-wÄqiâ€™ah. This study includes a qualitative study that is collecting data from words and not from numbers. While this type of research is a literature review, which examines and collects data by studying existing documents, for example books, magazines and others. In this study shows that in surah Al-wÄqiâ€™ah there are several muhassinÄt al-maâ€™nawiyah, including: al-á¹¬ibÄq, murÄ'atu al-Naáº“ir, irá¹£Äd, etc.